Prevalence and factors associated with smoking among medical students in a local university - Gyanchand Rampal, Lekhraj Rampal; David, N. C. E.; Lau, J. H. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Introduction: Smoking is the most preventable cause of death. Between 80,000 to 100,000 children worldwide are estimated to start smoking every year. Objectives: To determine the prevalence of smoking among medical students and determine the relationship between smoking and age, sex, race, religion, household income, media influence, peer and parental smoking status. Material and Methods: A cross-sectional study design was used in this study. All the 438 UPM medical students from Year 1to Year 5 were included in this study. A pre-tested, self-administered questionnaire was used to collect the data. The variables examined were age, sex, ethnicity, household income, religion, peer influence, family influence, smoking status, age started smoking, duration of smoking and quit attempts. Data was analysed using SPSS. Results: the overall prevalence of ever and current smokers was 19.3% and 2.4% respectively. The overall mean initiation age was 13.8% years (95% CI 12.7 – 14.(). All the 10 current smokers were males. Of the 10 current smokers, 2 were daily smokers while the remaining 8 were occasional smokers. Both the daily smokers were Malays. The 8 occasional smokers consisted of four Malays, 2 Indians, 1 Chinese and 1 of other race. The percentage of respondents who had at least one of their immediate family members who smoked was significantly higher among the ever smokers than the never smokers (p<0.05). The percentage of respondents who thought advertisement sponsored by cigarate companies influenced other to smoke was significant association between smoking and sex, peer influence, family influence and media influence. Conclusion: The prevalence of smoking among medical students in Universiti Putra Malaysia is relatively low compared to the national prevalence.